Ethical considerations in emergency medical services (EMS): understanding the significance of confidentiality - a scoping review - Aung, Khin Thandar; Abdul Razak, Rafiza; Aung, Thurein (Universiti Kuala Lumpur (UniKL), 2024)
Emergency Medical Services (EMS) play a critical role in the healthcare system, providing immediate care to individuals in life-threatening situations. The ethical principle of confidentiality is a cornerstone of healthcare that extends to prehospital care settings. This scoping review examines EMS confidentiality, explores its ethical implications, and its application considerations. PRISMA-ScR criteria were used for this scoping review. PubMed, Scopus, and Google Scholar were searched for literature. The search terms were “EMS,” “emergency medical services,” “confidentiality,” “ethics,” and “ethical considerations.” Empirical studies, review papers, EMS ethics, and rules of confidentiality were included in this review. Studies that did not address EMS ethics or confidentiality were excluded. The findings reveal that EMS confidentiality is influenced by ethical, legal, and practical factors. Legal and ethical frameworks, patient privacy and dignity, and practical challenges in EMS settings illuminated the need for confidentiality in EMS. This scoping review emphasises the need for confidentiality in EMS and the complexity of ethical issues. Understanding the importance of confidentiality in prehospital treatment can help design rules of ethics, policies, and training programmes for EMS providers. Further research is needed to identify challenges and develop techniques for maintaining confidentiality in various EMS scenarios to provide the best patient care while protecting their privacy.